The Effect of Self-Explanation Learning Strategies on Students’ Understanding of Mathematical Concepts - Awalludin, Subhan Ajiz; Sahab, Fahmi; Saelim, Rattikan (International Journal of Geometry Research and Inventions in Education, 2025)
This study investigates whether a structured self‑explanation strategy improves secondary students’ conceptual understanding of geometric transformations. Employing a quasi‑experimental nonequivalent posttest‑only control group design, the research sampled two intact eleventh‑grade classes from a public high school. The experimental class received worksheet-embedded prompts guiding them through four phases of self-explanation, whereas the control class experienced conventional instruction. Assumption checks confirmed normality and homogeneity, and an independent‑samples t‑test compared posttest performance. Students taught with self-explanation achieved higher scores on a five-item open-ended assessment of conceptual understanding than their peers in the control condition. The between‑group difference was statistically significant and accompanied by a large effect size (ES ≈ 0.83), indicating meaningful practical gains. Qualitative interpretation of score patterns suggests that explanation prompts facilitated integration across symbolic, graphical, and spatial representations and reduced common misconceptions in transformation tasks. These results align with prior evidence that metacognitive scaffolds deepen conceptual learning and support transfer beyond taught procedures. The findings imply that brief, structured self‑explanation can be feasibly integrated into routine lessons to enhance conceptual outcomes. Future research should explore retention over time, effects across diverse topics, and the comparative benefits of alternative metacognitive supports.